A Study on the Impact of Work- Study balance on academic performance among Expatriate students in Higher education institutions of Finland - Shiraz, Hirushi Tharika (My University, 2025)
The growing tendency to experience work-study balance issues among expatriate stu-dents in higher education highlights the influence on academic performance and well-being. This study investigates how expatriate students at Finnish higher education insti-tutions balance job and academic responsibilities and its impact on their academic per-formance. Data for the study were collected using a semi structured interview, with 31 expatriate students representing different academic streams and different nationalities. The findings show that, while work gives vital skills and financial security to students, it frequently undermines their academic performance and raises stress, underlining the importance of supportive institutional measures to promote student achievement.
Keywords: fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development